Multinationality, R&D and Productivity Evidence from the top R&D investors worldwide - Davide Castellani; Sandro Montresor; Torben Schubert; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2015)
The paper investigates the impact that the multinational scope of firms' activities can have on their productivity. First, we argue that such an impact is both direct and indirect, and that the latter is channelled through higher incentives to invest in R&D. Second, we posit that the composition of these direct and indirect effects is different if multinationality is measured at the intensive margin (higher share of multinational on total activities) rather than at the extensive margin (greater geographical dispersion of multinational activities). Using a large sample of top R&D investors in the world, we propose an econometric model based on an R&D and a productivity equation, which are both allowed to depend on multinationality. With this model we can disentangle the direct and indirect effects of multinationality on productivity appropriately. We find: i) a positive direct impact of multinational intensity on productivity, while the geographical dispersion of multinationality is negatively correlated with productivity; ii) multinationality (along both dimensions) has a positive indirect impact through higher investments in R&D; iii) this positive indirect effect is however not large enough to compensate the negative direct one at the extensive margin. Results are largely consistent with a theoretical approach that combines transaction cost theory with an economic analysis of how incentives to invest in R&D depend on multinationality.
Keywords: F23; F61; O32; 330; Multinationality; R&D; Productivity; Europe